Materials Development in the Colombian Context: Some Considerations About Its Benefits and Challenges - Bertha Ramos Holguín; Jahir Aguirre Morales (Asociación Colombiana de Profesores de Ingles, 2014)
Materials development is a field of study which has recently acquired significant importance in the Colombian context due to the fact that teachers, as materials developers, consider materials development as an area of knowledge that helps them to improve their teaching practices. However, the rationale, the gains as well as the challenges that drive materials designers have not been explored enough in Colombia. This article aims to provide some general considerations about the benefits teachers, as material developers, will obtain and some of the shortcomings which may emerge along this process. Finally, the authors discuss some implications for teachers, students, and teacher education programs.